MICROALBUMINURIA AND ITS CORRELATION WITH GLYCEMIC CONTROL IN TYPE 2 DIABETIC PATIENTS - Muhammad, Riaz; Rahman Afridi, Muhammad Abdur; Ali, Zafar; Asghar, Muhammad; Hussain, Lal; Rahman, Syed Kashif Ur; Alam, Intekhab (Journal of Postgraduate Medical Institute, 2018)
Objective: To find out the frequency of microalbuminuria and its correlation with glycemic control in type 2 diabetic patients presenting to a teaching hospital. Methodology: This descriptive study was carried out from March 2011 to April 2012, in the Department of Medicine, Lady Reading Hospital, Peshawar. The study included 121 type 2 diabetic patients of both genders above 30 years of age. Frequency of microalbuminuria was detected among these patients. Demographic and clinical details were recorded regarding microalbuminuria, duration of diabetes, glycated hemoglobin (HbA1c), blood glucose, gender and age. For data entry and analysis, SPSS version 21.0 was utilized. Chi-square test and boxplots were used for comparison of data and determining the relationship of microalbuminuria with glycemic control. Results: There were 47 (38.8%) males and 74 (61.2%) females in the present study. Mean age of study patients was 54.21 ±10.27 years (range 30-80 years). Microalbuminuria was present in 73 (60.3%) patients. Average duration of diabetes was 5.809 ±3.55 years and average HbA1c was 8.55 ±1.24%. There was significantly increased frequency of microalbuminuria in poorly controlled diabetics (83.56%) compared to diabetics with good glycemic control (16.44%), p value 0.015. Conclusion: Microalbuminuria was found with increased frequency in type 2 diabetic patients. The relationship of microalbuminuria with glycemic control and duration of diabetes mellitus was statistically significant.